2006
DOI: 10.1191/0748233706th252oa
|View full text |Cite
|
Sign up to set email alerts
|

Levels of retinyl palmitate and retinol in stratum corneum, epidermis and dermis of SKH-1 mice

Abstract: Vitamin A (retinol) regulates many biological functions, including epidermal cell growth. Retinyl palmitate (RP) is the major esterified form of retinol and the predominant component of retinoids in the skin; however, how endogenous levels of RP and retinol in the skin are affected by the age of the animal remains unknown. Furthermore, the levels of retinol and RP in the various skin layers - the stratum corneum, epidermis and dermis of skin - have not been reported. In this paper, we report the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The skin recovery method for retinol was developed by Yan et al . . This method was used and slightly modified for all other antioxidants in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The skin recovery method for retinol was developed by Yan et al . . This method was used and slightly modified for all other antioxidants in this study.…”
Section: Methodsmentioning
confidence: 99%
“…We (Yan, et al, 2006a) have previously shown that levels of both RP and retinol in the skin of naive SKH-1 female mice are age-dependent. In the subsequent studies, we (Yan, et al, 2006b) examined the accumulation and disappearance of RP and retinol in female SKH-1 mice that received a single or repeated (two, three, or six) daily topical cream applications of RP (0.5 or 2%, w/w).…”
Section: Introductionmentioning
confidence: 90%
“…RP and retinol analysis of stratum corneum, epidermis, and dermis Stratum corneum, epidermis, and dermis skin layers were separated from the mice untreated and treated with RP as previously reported (Yan, et al, 2006a). Following the procedures described previously (Yan, et al, 2006a,b), each tape strip from the stratum corneum layers was extracted with ethanol for 30 min at 6°C.…”
Section: Analysis Of Skin Rp and Retinolmentioning
confidence: 99%
“…RP is the major esterified form of retinol and accounts for >90% of the retinyl esters endogenously formed in skin. As retinyl esters are more chemically and thermally stable than retinol, retinyl esters are preferred retinoid used in skin care products, and are commercially used as an ingredients in cosmetic products (Yan et al , 2006a; Yan et al , 2006b).…”
Section: Introductionmentioning
confidence: 99%